2012
DOI: 10.1136/postgradmedj-2012-131226
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills and attitudes of doctors towards assessing cognition in older patients in the emergency department

Abstract: Doctors reviewing patients in the emergency department-setting reported several important factors limiting their ability to screen older patients for cognitive impairment. Respondents to this questionnaire did not feel the emergency department environment was conducive towards the assessment of cognition in older patients. Clarification of each discipline's responsibility in the detection, assessment and management of delirium and/or dementia, and the implementation of emergency department cognitive screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
1
43
0
1
Order By: Relevance
“…Dalam beberapa penelitian, pasien usia lanjut datang ke IGD dengan presentasi klinis yang atipikal dan belum tentu disertai dengan perubahan tanda vital. 9,10 Oleh karena itu, validasi skor REMS untuk populasi khusus ini penting dilakukan. …”
Section: Pendahuluanunclassified
“…Dalam beberapa penelitian, pasien usia lanjut datang ke IGD dengan presentasi klinis yang atipikal dan belum tentu disertai dengan perubahan tanda vital. 9,10 Oleh karena itu, validasi skor REMS untuk populasi khusus ini penting dilakukan. …”
Section: Pendahuluanunclassified
“…Assessment rates for cognitive impairment and recording of such are typically low in the ED environment 8 18. While most physicians feel that screening cognition in the ED is important, many feel that time constraints, the physical infrastructure of the ED and concerns over privacy and noise deem the ED environment unsuitable for assessing cognition 18.…”
Section: Introductionmentioning
confidence: 99%
“…While most physicians feel that screening cognition in the ED is important, many feel that time constraints, the physical infrastructure of the ED and concerns over privacy and noise deem the ED environment unsuitable for assessing cognition 18. In one report, only 28% of patients with impaired cognitive function had this documented, 70% of whom had no prior history of dementia 8.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive examination skills too may not be well taught. In a study of emergency settings, a majority of emergency physicians identified cognitive screening as important but a third believed they lacked the expertise to conduct a cognitive screen (Kennelly et al, 2013).…”
Section: Psychiatry and Deliriummentioning
confidence: 99%